ANALISIS FAKTOR MOTIVASI, OPPORTUNITY, ABILITY DAN KINERJA PETUGAS PROGRAM KESEHATAN IBU DI PUSKESMAS - Rossalina Adi Wijayanti; Novita Nuraini (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2018)
Maternal Mortality Rate (MMR) turns out to be a problem that has not been solved in the world. Jember regency ranked second highest in east java in 2016. Puskemas Karang Duren in Jember regency has MMR in 2011, 2012, 2013. Promotive and preventive effort through the continuing approach has been implemented to make the MMR stable. For example by developing the maternal healthcare program with the use of mother card as their pregnancy medical record. This research intends to analyze motivation, opportunity, ability, and performance maternal healthcare program in Puskesmas. It uses analityc observational cross sectional design as the research method. There were 10 midwives as the research sample obtained by simple random sampling technique. It was analyzed by applying the data tabulation software. This result found out that most of the midwives were average in their motivation (60%), they were sufficient in the opportunity (60%), they were good in the ability (80%), and they were performance maternal healthcare program belongs to good category (80%). It shows that there were significant relationship between opportunity, ability, and the performance maternal healthcare program. Hence, the recommendation was formed by brainstorming activity involving the entire midwives and the head of the Community Health Center. It can be conducted by giving motivation (praising during meeting, warning, and guidance from the chiefs). It surely needs the uniformity of this medical recording format to make the supervision activity, monitoring, and evaluation goes easier later on. All of the sides are expected to be involved in maintaining the MMR.